Heating Duration and Stabilizers Determine Red Dragon Fruit Marmalade Quality: Durasi Pemanas dan Stabilisator Menentukan Kualitas Selai Buah Naga Merah - Anastasya Virnanda; Syarifa Ramadhani Nurbaya (Academia Open, 2025)
General Background: Red dragon fruit (Hylocereus polyrhizus) is rich in bioactive compounds but has high moisture content and limited shelf life, necessitating processing into semi-wet products such as marmalade. Specific Background: The quality of marmalade is closely related to thermal processing conditions and the use of stabilizing agents that govern gel formation, consistency, and sensory acceptance. Knowledge Gap: Limited information is available regarding how variations in heating duration and stabilizer type jointly determine the organoleptic characteristics of red dragon fruit marmalade. Aims: This study aimed to determine the combined role of heating time (20, 40, and 60 minutes) and stabilizer type (CMC 0.4%, pectin 0.4%, carrageenan 0.4%) on sensory properties of the product. Results: Factorial randomized block analysis revealed a significant interaction on texture and spreadability, while color, aroma, and taste showed no statistically significant differences across treatments.  Novelty: The study provides comparative organoleptic evidence for three commonly used hydrocolloids under controlled thermal regimes in red dragon fruit marmalade processing. Implications: These findings offer practical guidance for food technologists and small-scale processors in selecting appropriate heating conditions and stabilizers to obtain desirable sensory characteristics while utilizing perishable tropical fruit resources. Highlights: Interaction of processing variables was significant for texture and ease of spreading. Visual appearance, aroma perception, and flavor acceptance remained statistically similar across treatments. Longer thermal exposure produced firmer gel structure and darker product appearance. Keywords:Red Dragon Fruit; Marmalade; Heating Time; Stabilizer Type; Organoleptic Properties